Analisa kepuasan pengguna terhadap Aplikasi ThatQuiz dengan Metode WebQual 4.0 - Hairun Anisyah; Tata Sutabri (LPPM UBHINUS MALANG, 2023)
SMKN 5 Palembang is a school that has begun to utilize information technology in its teaching and learning process, this can be seen from the implementation of e-learning as a supporting medium in teaching and learning activities. Apart from the e-learning, in the process of evaluation or school exams, several teachers have implemented an information technology-based exam system, namely the application thatQuiz which can be accessed via the internet either with a PC or mobile device. To measure the quality of a system or website whether it can be said to be good or not can be seen from the level of user satisfaction with the system. The webqual method is one of the most appropriate methods and is widely used in measuring the quality of a system. The way the method works is seen based on the processed results of the questionnaire data which is the opinion of the users which is compiled based on 4 important variables, namely the aspects of use, the quality of the information, the quality of system and user interaction and the general quality of the system. The purpose of this research is to get the results from the analysis of user satisfaction using the ThatQuiz application using the Webqual method. The results obtained later are the answers to the temporary hypotheses that the authors produce. The result is that the information variable has a significant positive effect on satisfaction, although the effect is small, the interactive variable has a significant positive effect on satisfaction, with a moderate effect according to the F test.